IMPLEMENTASI PEMBELAJARAN PAKEM PADA MATERI LUAS DAN KELILING BANGUN DATAR - Rora Rizky Wandini (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
Implementation of PAKEM learning model in widespread material and periphery with a general overview of the activities are: at the beginning of the teacher's learning condition class, the teacher's core activities explain the material by using the song learning and game quickly responsive, at the end of the activity can be done by meriview and evaluate learning. Improved student learning outcomes PGMI 1 UIN-SU on the mathematics of widespread material and circumference increased evidenced by the results of learning obtained before the given action and after being given around 80%, it unravel from the beginning before the action up to 2 people who answered correctly and 33 the wrong answer, in cycle 1, 15 people answered correctly and 20 people answered wrong, in cycle 2, 30 people answered correctly and 5 people answered wrong.